Keeping Children in School: The Response of the Montreal Catholic School Commission to the Depression of the 1930s - Johnston, Wendy (Historical Papers / Communications historiques)

(untitled) (The Canadian Historical Association/La Société historique du Canada, 1985)
AbstractIn Quebec, as elsewhere in Canada, the depression of the 1930s highlighted the inadequacies of existing welfare arrangements and ultimately compelled a shift towards greater state intervention and rationalization of philanthropy. Historians have so far devoted little attention to the situation of children and the evolution of child welfare services during this crucial period. This paper seeks to examine the effects of the depression on the origins, the nature and the impact of aid policies in a particular urban school system. The analysis centres on the Montreal Catholic School Commis- sion (MCSC), the largest of Quebec's local public school boards, during the period 1929 to 1940. In 1930, the Commission s primary and secondary schools boasted an enrolment of nearly one hundred thousand students. These mainly French-speaking children of working-class origin were particularly hard hit by the economic crisis.The author argues that the severe physical want experienced by schoolchildren in the depression years constituted a formidable obstacle to regular school attendance and to learning. Faced with this situation, MCSC officials were obliged to abandon a conception enshrining education, health and welfare as separate categories. The economic crisis thus compelled the commission to assume an enlarged, systematized and diversified role in student welfare. School authorities rationalized and expanded the long-standing policy of free schooling for indigents and, in 1934, created a social service agency to provide free milk and clothing to needy children. To this end, they allied a continuing reliance on private charity with the adoption of modern social work practices. However, lacking sufficient funding, MCSC assistance programmes proved hopelessly unequal to the enormous student need. The MCSC s depression-era ini- tiatives were, despite their inadequacies, developments of long-term significance, providing the springboard for social work's entry into the school system.